The psychology of Esports: A systematic literature review - Bányai, F.; Griffiths, M. D.; Király, O.; Demetrovics, Z. (Journal of Gambling Studies, 2018)
Recently, the skill involved in playing and mastering video games has led to the professionalization of the activity in the form of `esports` (electronic sports). The aim of the present paper was to review the main topics of psychological interest about esports and then to examine the similarities of esports to professional and problem gambling. As a result of a systematic literature search, eight studies were identified that had investigated three topics: (1) the process of becoming an esport player, (2) the characteristics of esport players such as mental skills and motivations, and (3) the motivations of esport spectators. These findings draw attention to the new research field of professional video game playing and provides some preliminary insight into the psychology of esports players. The paper also examines the similarities between esport players and professional gamblers (and more specifically poker players). It is suggested that future research should focus on esport players` psychological vulnerability because some studies have begun to investigate the difference between problematic and professional gambling and this might provide insights into whether the playing of esports could also be potentially problematic for some players.